2017
DOI: 10.15586/jkcvhl.2017.56
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Histone Demethylases in Renal Cell Carcinoma

Abstract: Renal cell carcinoma (RCC), the most common kidney cancer, is responsible for more than 100,000 deaths per year worldwide. The molecular mechanism of RCC is poorly understood. Many studies have indicated that epigenetic changes such as DNA methylation, noncoding RNAs, and histone modifications are central to the pathogenesis of cancer. Histone demethylases (KDMs) play a central role in histone modifications. There is emerging evidence that KDMs such as KDM3A, KDM5C, KDM6A, and KDM6B play important roles in RCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…The set of constraints (12)(13)(14)(15)(16)(17)(18) ensures that all ancestor-descendant pairs of nodes in T S represent high-confidence temporal orderings. Specifically, constraint (18) eliminates from consideration all such pairs with insufficient support from tumor graphs.…”
Section: Ordering Nodes Into a Conserved Evolutionary Trajectory Treementioning
confidence: 99%
See 2 more Smart Citations
“…The set of constraints (12)(13)(14)(15)(16)(17)(18) ensures that all ancestor-descendant pairs of nodes in T S represent high-confidence temporal orderings. Specifically, constraint (18) eliminates from consideration all such pairs with insufficient support from tumor graphs.…”
Section: Ordering Nodes Into a Conserved Evolutionary Trajectory Treementioning
confidence: 99%
“…Specifically, constraint (18) eliminates from consideration all such pairs with insufficient support from tumor graphs. We introduce auxiliary variables P A u,v,w , set to 1 if u is an ancestor of w and w is an ancestor of v and set to 0 otherwise -by constraints (12), (13) and (14). A parent of a node is its ancestor by default, by constraint (15).…”
Section: Ordering Nodes Into a Conserved Evolutionary Trajectory Treementioning
confidence: 99%
See 1 more Smart Citation
“…Renal cell carcinoma (RCC) is a common malignant tumor of the urinary system, accounting for 2%–3% of adult malignancies, 1 and more than 100,000 people die of kidney cancer every year worldwide. 2 The most common subtype of RCC is clear cell renal cell carcinoma (ccRCC), which is associated with high morbidity and poor prognosis. 3 …”
Section: Introductionmentioning
confidence: 99%
“…KDM3A (also known as JHDM2A or JMJD1A) is a histone demethylase that physically interacts with the androgen receptor (AR) to upregulate AR target gene expression through the demethylation of methylated histone H3 lysine 9 ( 76 ), a modification that is generally associated with transcriptional repression. More recent studies have revealed that histone lysine demethylases such as KDM3A play important roles in renal cell carcinoma, the most common kidney cancer, via hypoxia-mediated angiogenesis pathways ( 77–79 ). Smad3 is an intracellular signal transducer and transcriptional modulator activated by transforming growth factor (TGF)-β ( 80 ).…”
Section: Discussionmentioning
confidence: 99%